Pengaruh Modal, Tingkat Upah dan Teknologi terhadap Penyerapan Tenaga Kerja dan Produktivitas pada Industri Sablon di Kota Denpasar - Prabawa, A A Ngurah Panji; Sri Budhi, I Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 7, Juli 2017 (pp. 1157 - 1394), 2017)
The purpose of this study was to analyze and determine 1) The direct effect of capital, wages and technology on employment, 2) The direct effect of capital, wages, technology and employment on productivity, 3) The indirect effect of capital, the level of wages and technology on productivity through employment. This research was conducted in Denpasar with printing industry employers respondents covering 4 consisting of Denpasar District of North, West Denpasar, Denpasar Denpasar South and East. Object in this research include the capital, wages and technology. The sampling technique used is Proporsionate Stratified Random Sampling. Data collection methods used in this study include observation, interviews and in-depth interviews. Data analysis technique used is path analysis, path analysis and Sobel test to analyze the indirect influence through an intervening variable. The results showed capital, wages and technology and significant positive effect on employment sablon industry
Keywords: Modal,Tingkat Upah, Teknologi, Penyerapan Tenaga Kerja, Produktivitas